Glavlit in Lithuania, 1953–1964 - Pukinskaitė, Jurga (Genocidas ir rezistencija, 2004)
The censorship institutions intended to maintain the monopolistic control of public life were one of the most important supporting structures of Soviet ideology. On the basis of archival material relating to the Glavlit of the Lithuanian SSR, which carried out censorship in Lithuania, the activities of the republic's Glavlit in the post-Stalin times in between 1953 and 1964, the periods of its most intensive activity are analysed and reviewed in this article.As the leaders of the USSR and the country's international position were changing during this period, new ideological priorities emerged, and relations of the Party's governing structures with intellectuals became directly dependent on the change in the Party's leadership. At the beginning of the rule of both Nikita Khrushchev and Leonid Brezhnev, cultural matters were neglected; temporary upheavals also took place, which created conditions for a brief period of freedom. After Stalin's death, a more humane policy was especially noticeable in cultural life, although the after effects of the personality cult still strongly repressed any freer thought. However, more works of Lithuanian classics and the classics of other nations were allowed to be published, political and cultural initiatives could be expressed more openly. People tried to avoid censorship, reorganise the system of culture and educational institutions and rebuild some historic and cultural monuments. Post-Stalin liberalisation brought relief to Lithuanian intellectuals in the creative arts – the Communist Party and Glavlit began to tolerate ideologically neutral works; the primitive nature of Stalinist culture could be discarded. Although bureaucratic centralisation did not allow artists to express themselves fully, the abandonment of repressive policy encouraged the creativity of many intellectuals.However, such temporary breaks merely signified a search for new forms of control; a new ideological platform was being created. In 1957, when information about the events in Hungary and Poland reached Lithuania, more attention was paid to ideological works and attempts to create a uniform Soviet culture became more active. Centralised Communist cultural policy based on a class perspective did not tolerate any manifestations of nationalism, while criteria for the evaluation of art followed the benchmarks of socialist realism. Creative works issued during the "thaw" were returned to special funds and intellectuals in the arts were forced to participate more actively in propaganda campaigns. Once again the unity of the Soviet Union was stressed; manifestations of local identity were suppressed, slogans of "revolutionary vigilance" were raised and work of the censors again intensified. At the beginning of the 1960s the KGB became more interested in censorship. Khrushchev's speeches against formalism and impressionism in the arts became a basis for suppressing manifestations of Western culture.
Keywords: Soviet occupation; cenzorship; Glavlit; culture; press